HEALTH EDUCATION IN MEXICO - GARZA BRITO, ANGEL DE LA (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1948)
Oiketicoides tristis, Eurukuttarus conjederata, E polingi, E hoffmanni, and Platoeceticus gloveri are discussed Geographic distribution and food plant are given whenever possible Caterpillars, bags, etc, are described with drawings; photographs of th
AM J VET RES
Keywords: HEALTH EDUCATION, MEXICO; CIENCIAS MEDICAS; SALUD PUBLICA; EDUCACION SANITARIA